A Baltic Struggle for a "European Memory": The Militant Mnemopolitics of The Soviet Story. Issue 4 (2nd October 2018) - Mälksoo, Maria
ABSTRACT: This article examines the Latvian documentary The Soviet Story (by Edvīns Šnore, 2008) as a militant Baltic memory project which seeks to establish the parity of East and West European experiences with totalitarian crimes in the pan-European memory narrative of twentieth-century wars and genocide. The film offers a useful vantage point for investigating the interaction between memory politics and identity-building across the post-communist space and beyond. Claiming the inner similarity and moral equitability of Soviet communism and German National Socialism, The Soviet Story constitutes an epitome of the Historikerstreit in the Baltic fashion, debating the uniqueness of the Holocaust next to the crimes of communism. The so-called Holocaust template has been essential for the makers of the documentary in their insisting on the pan-European condemnation of totalitarian communist regimes in Europe, along with an invitation to critically review the role of the USSR in the Second World War. The Soviet Story is particularly critical about the Western discriminative standard of remembering the mass killings of Nazi Germany and the USSR, claiming such position's unsustainability on intellectual, moral, and political grounds. The article investigates The Soviet Story as an example of the cultural front in the Baltic-Russian "memory war" over remembering the Soviet legacy, reading the film's message in the context of the broader East European politics of seeking pan-European condemnation of the crimes of totalitarian communist regimes. It further discusses the transnational efficacy of such mnemopolitical projects against the backdrop of intensified activity on the information operations front in the Baltic-Russian relations in recent years.